2018
DOI: 10.5858/arpa.2017-0571-ra
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Human Papillomavirus Infections

Abstract: - The low-risk HPV types 6 and 11 appear to play a role in the development of at least a subset of conjunctival squamous papillomas. The role of HPV in the pathogenesis of pterygium and ocular surface squamous neoplasia is less well defined. There is evidence to suggest that HPV may be a cofactor in the development of these lesions, acting in concert with ultraviolet radiation and/or human immunodeficiency virus infection in a subgroup of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 58 publications
1
9
0
18
Order By: Relevance
“…Detection of HPV DNA in pterygia in some studies may have been due to contaminated samples. Sonnex et al reported that HPV from genitalia was transmitted via finger-genital contact 9 , and many studies have mentioned this mechanism of autoinoculation between HPV in the genital area and ocular surfaces, including pterygia 3,22,[24][25][26] . However, in this study, HPV in the genital tract was not associated with HPV-infected conjunctiva or pterygia.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of HPV DNA in pterygia in some studies may have been due to contaminated samples. Sonnex et al reported that HPV from genitalia was transmitted via finger-genital contact 9 , and many studies have mentioned this mechanism of autoinoculation between HPV in the genital area and ocular surfaces, including pterygia 3,22,[24][25][26] . However, in this study, HPV in the genital tract was not associated with HPV-infected conjunctiva or pterygia.…”
Section: Discussionmentioning
confidence: 99%
“…HPV has already been implicated as a promotor of the development of both benign and malignant sebaceous tumors [31,32]. Squamous dysplasia of the conjunctiva and the lacrimal sac has also been shown to be associated with HPV [33,34]. DNA MMR nuclear protein expression was intact in the tumor cells for MSH6, MSH2, MLH1, and PMS2, thereby failing to implicate the Muir-Torre syndrome [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Ätiologie Am häufigsten ist die CIN an der bulbären Bindehaut zu sehen, passend zu der Tatsache, dass UV-Strahlung den pathogenetischen Hauptfaktor darstellt. HPV scheint neben UV-Strahlung in manchen Fällen ein pathogenetischer Ko-Faktor zu sein [23,24], der Zusammenhang wird aber im Gegensatz zu dem Pendant der Zervix kontrovers diskutiert.…”
Section: Konjunktivale Intraepitheliale Neoplasie (Cin)unclassified